A Short Introduction to DOAJ - Mitchell, Dominic; Aspaas, Per Pippin (Open Science Talk, 2022)
The Directory of Open Access Journals (DOAJ) was founded by Lars Bjørnshauge in 2003; the current managing director is Joanna Ball. A cornerstone in the global Open Science landscape, DOAJ currently lists more than 18,000 peer-reviewed, strictly open access journals (Gold or Diamond). Dominic Mitchell, who has worked for DOAJ for the last ten years, explains how the indexing process is managed by a combination of volunteers and salaried staff like himself, how they work to exclude predatory journals from the list, and how DOAJ is financed. Furthermore, DOAJ is involved in several collaborative projects promoting high-quality scholarly publishing, including The Principles of Transparency and Best Practice in Scholarly Publishing (4th ed., 2022). Recording made during the 17th Munin Conference on Scholarly Publishing. First published online: December 30, 2022.